2017
DOI: 10.3390/ijms18020455
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Repetitive Transcranial Magnetic Stimulation (rTMS) Improves Functional Recovery by Enhancing Neurogenesis and Activating BDNF/TrkB Signaling in Ischemic Rats

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has rapidly become an attractive therapeutic approach for stroke. However, the mechanisms underlying this remain elusive. This study aimed to investigate whether high-frequency rTMS improves functional recovery mediated by enhanced neurogenesis and activation of brain-derived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) pathway and to compare the effect of conventional 20 Hz rTMS and intermittent theta burst stimulation (iTBS) on ischemic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 46 publications
8
81
2
3
Order By: Relevance
“…On one hand, studies on the effects of rTMS on depression and autism have shown that specific sites and frequencies of rTMS promote the release of endogenous GABA as well as reduce the loss of GABA A R on the postsynaptic membrane, thereby increasing the efficacy of GABAergic neurons (Dubin et al, ; Tan et al, ). Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF‐TrkB receptor pathway in the brain (Guo et al, ; Luo et al, ). On the other hand, neuroimaging and TMS measure showed cortical hyperactivity in the several types of sleep orders (Lanza, Cantone, et al, ; Lin et al, ; Nardone et al, ; Salas et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On one hand, studies on the effects of rTMS on depression and autism have shown that specific sites and frequencies of rTMS promote the release of endogenous GABA as well as reduce the loss of GABA A R on the postsynaptic membrane, thereby increasing the efficacy of GABAergic neurons (Dubin et al, ; Tan et al, ). Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF‐TrkB receptor pathway in the brain (Guo et al, ; Luo et al, ). On the other hand, neuroimaging and TMS measure showed cortical hyperactivity in the several types of sleep orders (Lanza, Cantone, et al, ; Lin et al, ; Nardone et al, ; Salas et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, studies of rTMS in cognitive impairment and dyskinesia after stroke have shown that rTMS has an effect on the BDNF-TrkB receptor pathway in the brain (Guo et al, 2017;Luo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the agonistic effect and upregulation of NMDA receptors by rTMS may improve the cognitive impairment. Second, a recent study showed that high-frequency rTMS may improve the impaired neuronal plasticity by activating BDNF pathway in ischemic rats 38 . Thus, highfrequency rTMS may improve cognitive deficits in SCZ patients by activation of neurotrophic factors, which play critical roles in neuroplasticity in the hippocampus related to learning and memory 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We cannot answer it directly. According to animal studies, the regeneration processes are based on the elevation of brain derived nerve factor (BDNF) (Müller et al, 2000;Cheeran et al, 2008;Antal et al, 2010) and the increased production of progenitor cells (Arias Carrión, 2008;Guo et al, 2014;Ueyama et al, 2011;Liu et al, 2015aLiu et al, , 2015bLuo et al, 2017). Stimulation with 1 Hz was compared with 30 Hz of stimulation in the brains of adult mice (Abbasnia et al, 2015).…”
Section: Tablementioning
confidence: 99%